2008
DOI: 10.1007/bf03033506
|View full text |Cite
|
Sign up to set email alerts
|

Histamine H3 receptor ligands modulate L-dopa-evoked behavioral responses and L-dopa-derived extracellular dopamine in dopamine-denervated rat striatum

Abstract: To explore a recently established association between histaminergic and dopaminergic neuronal phenotypic systems in brain, we determined the effect of the respective histaminergic H(3) receptor agonist and antagonist/inverse agonist, imetit and thioperamide, on L-DOPA - derived tissue and extracellular DA and metabolite levels in the striatum of 6-hydroxydopamine (6-OHDA) - lesioned rats (i.e., parkinsonian rats). We also examined the influence of histamine H(3) ligands on L-DOPA evoked behavioral responses (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…As indicated by biochemical analysis, basal the histamine level was greatly altered in 6-OHDA-lesioned rats. It is noteworthy that in our recently published findings, thioperamide improved motor coordination in the rota-rod test in 6-OHDA rats and at the same time did not alter DA exocytosis in the striatum after L-DOPA (15 mg/kg IP) treatment (Nowak et al 2008a), while imetit did. In summary, the histamine H 3 receptor may represent a viable target for attenuation of motor disability in Parkinson's disease, either through direct action or via its ability to modulate the release of other neurotransmitters such as serotonin.…”
Section: Discussionsupporting
confidence: 45%
“…As indicated by biochemical analysis, basal the histamine level was greatly altered in 6-OHDA-lesioned rats. It is noteworthy that in our recently published findings, thioperamide improved motor coordination in the rota-rod test in 6-OHDA rats and at the same time did not alter DA exocytosis in the striatum after L-DOPA (15 mg/kg IP) treatment (Nowak et al 2008a), while imetit did. In summary, the histamine H 3 receptor may represent a viable target for attenuation of motor disability in Parkinson's disease, either through direct action or via its ability to modulate the release of other neurotransmitters such as serotonin.…”
Section: Discussionsupporting
confidence: 45%
“…This finding is consistent with previous observations. It was reported that thioperamide potentiated L-dopa-and methamphetamineinduced DA release in striatum and nucleus accumbens, respectively (Munzar et al 2004;Nowak et al 2008). Other antagonists of H 3 receptors, ABT-239 and GSK189254, increased DA levels in PFC and cingulate cortex, respectively (Fox et al 2005;Medhurst et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with our previous studies in which we showed that the baseline striatal extraneuronal (i.e., microdialysate) level of DA in 6-OHDA-lesioned rats varied between 3.2 and 3.6 pg/20 ll and that L-DOPA acutely produced a gradual increase in the microdialysate DA concentration, up to 160 pg/20 ll at 180 min, with a concomitant rise in DOPAC levels (from *0.65-0.75 ng/20 ll to *25 ng/20 ll) (Nowak et al 2008). Additionally, L-DOPA-derived DA in the in vivo microdialysates is several-fold higher in DA-denervated versus intact striatum (Kostrzewa et al 2005).…”
Section: Discussionmentioning
confidence: 94%